Euglycemic Diabetic Ketoacidosis in a Pregnant Patient on Insulin Pump Therapy - Hesham Yasin, MD; Jordan D. Ross, MD; James Turner, MD; Samuel Dagogo-Jack, MD, DSc (AACE Clinical Case Reports)
Background/Objective: Diabetic ketoacidosis is a common endocrine emergency. A subset of patients present with euglycemic diabetic ketoacidosis, which may be diagnosed late due to its rarity and relatively lower blood glucose levels. Pregnancy is associated with euglycemic diabetic ketoacidosis, which can lead to maternal and fetal demise without prompt treatment. The objective of this case report is to describe a patient with type 1 diabetes mellitus who developed euglycemic diabetic ketoacidosis on insulin pump therapy during pregnancy. Case Report: A 30-year-old pregnant patient at 33 weeks of gestation with type 1 diabetes mellitus on continuous subcutaneous insulin infusion presented to the emergency department with vomiting. Her serum bicarbonate of 9 mmol/L was accompanied by serum glucose of 130 mg/dL, moderate blood ketones, and urine ketones 80 mg/dL (large). She was treated with intravenous insulin infusion without complications to herself or the fetus. Discussion: Pregnancy is a common background for euglycemic diabetic ketoacidosis and can lead to maternal and fetal demise if not addressed early. Despite insulin resistance in pregnancy, a relatively low blood glucose is maintained by increased glycogen storage and increased fetoplacental uptake. Altered acid-base physiology in pregnancy may also increase the propensity for euglycemic diabetic ketoacidosis. Conclusion: Diabetic ketoacidosis can present in pregnancy with euglycemia, and a high index of suspicion is needed by both patients and health care teams. There are a few reports on this phenomenon in a pregnant patient using an insulin pump. Early identification and treatment are important to prevent maternal and fetal complications.